Effect of Fetal Hypothyroidism on Cardiac Myosin Heavy Chain Expression in Male Rats - Yousefzadeh,Nasibeh (2016)
Abstract Background: Thyroid hormone deficiency during fetal life could affect the cardiac function in later life. The mechanism underlying this action in fetal hypothyroidism (FH) in rats has not been elucidated thus far. Objective: The aim of this study is to evaluation the effect of FH on cardiac function in male rats and to determine the contribution of α-myosin heavy chain (MHC) and β-MHC isoforms. Methods: Six pregnant female rats were randomly divided into two groups: The hypothyroid group received water containing 6-propyl-2-thiouracil during gestation and the controls consumed tap water. The offspring of the rats were tested in adulthood. Hearts from the FH and control rats were isolated and perfused with langendroff setup for measuring hemodynamic parameters; also, the heart mRNA expressions of α- MHC and β-MHC were measured by qPCR. Results: Baseline LVDP (74.0 ± 3.1 vs. 92.5 ± 3.2 mmHg, p < 0.05) and heart rate (217 ± 11 vs. 273 ± 6 beat/min, p < 0.05) were lower in the FH rats than controls. Also, these results showed the same significance in ±dp/dt. In the FH rats, β-MHC expression was higher (201%) and α- MHC expression was lower (47%) than control. Conclusion: Thyroid hormone deficiency during fetal life could attenuate normal cardiac functions in adult rats, an effect at least in part due to the increased expression of β-MHC to α- MHC ratio in the heart.